Optimization in the Recovery of Zinc of polymethalic minerals through the flotation process in the company Mines and Metals Trading Perú - Huancavelica - Inga Paucar, Aroldo (2020)
The main objective of this research work was to optimize the recovery of zinc in the second stage of flotation of polymetallic minerals of the company Mines and Metals Trading Peru where its average annual recovery of zinc is 82%. At the concentrator plant, two samplings were carried out, the first one of fresh mineral in the belt No. 01 that feeds the primary grinding and the pulp were obtained from the bulk Pb / Ag flotation tails. During the study, preliminary flotation tests were carried out in order to select the most influential independent variables in the dependent variable using the MINITAB statistical program. Flotation tests were performed varying the dosage of copper sulfate (g / TM) and regrind time (minutes). With the results obtained, the optimization with the Hexagonal Design is carried out, obtaining maximum values of copper sulfate of 351.06 gr / TM and regrinding time of 5.06 minutes. With these results a theoretical recovery of 95.54% is obtained.